Pengaruh Kerjasama Tim terhadap Kinerja Pegawai di Akademi Maritim Cirebon - Fereddy Siagian (Alignment:Journal of Administration and Educational Management, 2020)
The purpose of this study is to find out and analyze studies on the effect of teamwork on employee performance. This research is a quantitative descriptive study with a total sample of 51 respondents, while the sampling technique uses probability sampling method using simple random sampling technique. The results showed that the teamwork variable was obtained by t count (13,170)> t table (2,011). Then the teamwork variable partially influences the employee performance variable, with a sig value of 0,000 <from the value of 0.05. With the value of R Square obtained results of 0.783, this means that teamwork variables influence the change in Y of 0.783 or in other words the effect of the independent variables on the dependent variable is 78.3% while the remaining 21.7% is caused by other variables not included researched within a research framework. Conclusion, the value of the Multiple Correlation Coefficient (R) obtained a value of 0.885 shows that there is a very strong joint relationship between the independent variables of Team Cooperation to the dependent variable, namely Employee Performance. Keywords: Team Cooperation, Employee Performance